Reformasi Birokrasi untuk Mewujudkan Birokrasi Kelas Dunia untuk Meningkatkan Pelayanan Publik di Jakarta - Utoyo, Arsa Widitiarsa; Razali, Geofakta; Saksono, Eko Hari (Magister of Communication Science, Sahid University Jakarta., 2022)
Utilization of information technology in realizing the bureaucracy to improve public services to the community is very important at this time, given the increasingly rapid development of technology. The development of information technology realizes the absence of clear boundaries between one region and another in Indonesia. Currently, how the government in Jakarta has been able to utilize information technology facilities and infrastructure to provide excellent service to the community. So that services can be provided quickly, precisely, and easily. The research method used in this study is qualitative research using a descriptive approach. This qualitative research is used to examine the condition of the object scientifically how the use of information technology can be able to provide changes to the public service bureaucracy in Jakarta so that services can be enjoyed by all levels of society.Â